EFEKTIVITAS Bacillus cereus DALAM KONVERSI LIMBAH PADAT KELAPA SAWIT MENJADI BIOETANOL SEBAGAI MATERI PEMBELAJARAN BIOTEKNOLOGI SMA KELAS XII - Jagad, Nur Jati (Guru Membangun, 2024)
The increase in world population and human activities are driving an increase in fossil energy consumption. This has an impact on the depletion of fossil energy reserves and exacerbates global warming. As an alternative, the use of palm oil waste to produce bioethanol can be an environmentally friendly solution. The purpose of this study was to determine the effect of adding Bacillus cereus bacteria concentration in the fermentation of palm oil solid waste on bioethanol levels, to determine the concentration of Bacillus cereus bacteria that can produce the highest bioethanol, to determine the potential of research results as learning materials for high school grade XII. This study is an experimental study with independent variables, namely the concentration of Bacillus cereus bacteria 0%, 5%, 7.5%, and 10% of 500 mL of substrate volume, while the dependent variables are the levels of reducing sugar and bioethanol levels. Reducing sugar is measured using the Nelson Somogy method while Bioethanol uses the micro conway diffusion method. Analysis of the potential of learning materials from the research results uses the principles of relevance, consistency, and adequacy. The results showed that the concentration of Bacillus cereus bacteria affected the levels of bioethanol from palm oil solid waste. The treatment of 5% concentration of Bacillus cereus bacteria produced the highest levels of reducing sugar and bioethanol. The resulting reduced sugar content was 0.0086% and the resulting bioethanol content  was 0.275%. The research results fulfill the principles of learning materials so that they have the potential to be used as biotechnology learning materials for class XII students